1996
DOI: 10.1111/j.1365-246x.1996.tb06534.x
|View full text |Cite
|
Sign up to set email alerts
|

Inelastic models of lithospheric stress-11. Implications for outer-rise seismicity and dynamics

Abstract: S U M M A R YOuter-rise seismicity and dynamics are examined using inelastic models of lithospheric deformation, which allow a more realistic characterization of stress distributions and failure behaviour. We conclude that thrust-and normal-faulting outer-rise earthquakes represent substantially different states of stress within the oceanic lithosphere. Specifically, the normal-faulting events occur in response to downward plate bending, which establishes the 'standard', bending-dominated state of outer-rise s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
2

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(50 citation statements)
references
References 105 publications
2
46
2
Order By: Relevance
“…Instead, in our modeling the inversion occurs over a maximum curvature point (Figure 10c). The reader is referred to the work by Mueller et al [1996a, 1996b] for further details on this subject.…”
Section: Modeling the Basin Evolutionmentioning
confidence: 99%
“…Instead, in our modeling the inversion occurs over a maximum curvature point (Figure 10c). The reader is referred to the work by Mueller et al [1996a, 1996b] for further details on this subject.…”
Section: Modeling the Basin Evolutionmentioning
confidence: 99%
“…[4] The relationship between interplate stress cycles and intraslab earthquake activity has been of interest, because it reveals intuitive aspects of stress transfer, faulting interactions, and seismic hazard that may be quantitatively modeled [e.g., Isacks et al, 1968;Stauder, 1968;Abe, 1972;Ruff and Kanamori, 1980;Christensen and Ruff, 1988;Dmowska et al, 1988;Lay et al, 1989;Liu and McNally, 1993;Dmowska et al, 1996;Taylor et al, 1996;Mikumo et al, 1999;King, 2007;Ammon et al, 2008;Lay et al, 2009]. However, it has also been shown that viscoelastic deformation can complicate the behavior [e.g., Mueller et al, 1996aMueller et al, , 1996bLay et al, 2009].…”
Section: Introductionmentioning
confidence: 99%
“…However, the strain rate associated with a specified tectonic process is determined by the ratio of accumulated strain and the accumulation time. Estimates of the accumulated strain determined by Mueller, Spence & Choy (1996), combined with a recurrence interval of the order of one century, indicate that the strain rate associated with in-plane-force variations is comparable to that associated with outer-rise flexure.…”
Section: Thermal Structure and Strain Ratementioning
confidence: 94%
“…Christensen & Ruff 1988). The manner in which either of these may lead to substantial levels of in-plane compression within the outer-rise complex is discussed in Mueller et al (1996). The loading sequence represented in Fig.…”
Section: Compound Plate-loadingmentioning
confidence: 99%
See 1 more Smart Citation